Revalidation of Platystigma Kennedy, 1920, with a synopsis of the quadratum species group and the description of three new species (Odonata: Pseudostigmatidae) - Machado, Angelo B. M.; Lacerda, Déborah S. Soldati (Zootaxa, 2017)
The genus Platystigma Kennedy, 1920 is revalidated based mainly on the third segment of the penis that is plate-like, whereas in the other Pseudostigmatidae it is a flagellum. Dijkstra et al (2014) have merged this family into the Coenagrionidae. However, we prefer to maintain the long-used name Pseudostigmatidae until more detailed phylogenetic studies with more sampling are done. Eight species are here considered in the genus, three of which are described as new: P. humaita, P. minimum and P. quadratum. The genus is divided in two species group, jocaste and quadratum, the latter studied here. The hitherto unknown male of P. martinezi (Machado 1985) is described for the first time. Evidence for exophytic oviposition is presented in at least one species of the genus. A key is provided for the species of the quadratum group.